Some production parameters of Blended goats in semi-arid regions of Tanzania - Lyatuu, Eliamoni T.R.; Das, S.M.; Mkonyi, J.I. (1994)
Data on blended goats (a three-way cross of Kamorai (55%), Boer (30%) and indigenous Tanzanian (15%) goats) were collected over a period of four years (1987-1990) at Malya and Kongwa Research Stations. These records were analysed to assess the production potential of Blended goats. Birth weights, weaning weights, weight at 72 weeks, milk yield, lactation length and butter fat content of milk were used as parameters.At Malya the average birth weight was 2.34 kg, the average weaning weight 12.5 kg and the average weight at 72 weeks was 28.0 kg. At Kongwa the averages were 2.31, 11.6 and 27.4 kg for birth weight, weaning weight and weight at 72 weeks, respectively. Milk yields ranged from 90.0 kg to 175.5 kg during an average lactation of 236 days. Season of kidding, age at kidding and birth type all significantly (P<0.05) influenced lactation yield. Average milk butter fat content for both stations was 2.9%.